Obstacles of Distance Education in Light of Corona Pandemic from the Point of View of Basic Education Teachers in Misurata - Altieb, Salima Omar ((Faculty of Arts Journal) مجلة كلية الآداب - جامعة مصراتة, 2021)
The research aims to know the obstacles of distance education in light of Corona pandemic (COVID-19) from the point of view of teachers of basic education in the city of Misurata. The researcher used the descriptive analytical method for its suitability to the nature of the research, The research sample consisted of (100) male and female teachers from a community of (300) male and female teachers from (8) schools, and a questionnaire was used as a tool to collect data represented in the responses of the research sample on the topic of the research and extracting its validity and reliability, and analyzing the sample responses statistically by means of arithmetic averages and standard deviations, and a one-way analysis of variance test for significance of differences. It also resulted in the absence of statistically significant differences due to the variables of years of experience.